2004
DOI: 10.1158/1055-9965.1005.13.6
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Biomarkers in Charcoal Workers Exposed to Wood Smoke in Bahia State, Brazil

Abstract: Charcoal is an important source of energy for domestic and industrial use in many countries. Brazil is the largest producer of charcoal in the world, with ∼350,000 workers linked to the production and transportation of charcoal. To evaluate the occupational exposure to wood smoke and potential genotoxic effects on workers in charcoal production, we studied urinary mutagenicity in Salmonella YG1041 +S9 and urinary levels of 2-naphthol and 1-pyrenol in 154 workers of northeastern Bahia. Workers were classified i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 37 publications
2
34
0
Order By: Relevance
“…The technique has been employed to assess urinary mutagenicity in subjects exposed to complex combustion emissions of coal and biomass fuels, selected industrial chemicals, and airborne particulate matter at urban and nonurban locations. More specifically, studies have assessed urinary mutagenicity in benzidine-exposed factory workers in India, wood smoke-exposed charcoal workers in Brazil, and wood-smoke-exposed individuals using traditional Native American saunas. These studies showed positive correlations between exposure metrics (e.g., duration) and urinary mutagenicity. ,, …”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…The technique has been employed to assess urinary mutagenicity in subjects exposed to complex combustion emissions of coal and biomass fuels, selected industrial chemicals, and airborne particulate matter at urban and nonurban locations. More specifically, studies have assessed urinary mutagenicity in benzidine-exposed factory workers in India, wood smoke-exposed charcoal workers in Brazil, and wood-smoke-exposed individuals using traditional Native American saunas. These studies showed positive correlations between exposure metrics (e.g., duration) and urinary mutagenicity. ,, …”
Section: Introductionmentioning
confidence: 87%
“…Mutagenic potency was calculated as the slope of the initial linear portion of the concentration− response function and expressed as rev/μmol of creatinine. 10,44 Urinary creatinine concentration was used to correct for urinary dilution.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations